Comparison of lymphocyte transformation and macrophage migration inhibition tests in the detection of beryllium hypersensitivity. - Williams, W R (1982)
In seven patients with chronic beryllium disease (Be) the Be lymphocyte transformation test was positive in 100%, independent of steroid therapy, and was reproducible. The Be macrophage migration inhibition test was only positive in four of seven patients (57%) not on steroids, and was not reproducible. In 72 potentially exposed healthy beryllium workers the lymphocyte transformation test was negative in all subjects. The macrophage test was positive in four of 78 and again the results were not reproducible. The workers with positive results showed no differences in age, type or duration of employment from those with negative results and showed no evidence of disease. In addition, the macrophage test was positive in two of 45 non-exposed control subjects. We also confirmed the above advantages of the lymphocyte transformation technique by using tuberculin antigen (PPD). The PPD lymphocyte transformation test gave positive results in approximately 60% of healthy beryllium workers, but the PPD macrophage test was only positive in 7%. We conclude that the Be lymphocyte transformation test is the most sensitive and reproducible and advocate its use in the diagnosis of disease and in monitoring the health of potentially exposed workers.